Determinants of rural multidimensional poverty of households in Southern Ethiopia - Fassil Eshetu; Jema Haji; Mengistu Ketema; Abule Mehare (Cogent Social Sciences, 2022)
Some studies have quantified the extent and examined the determinants of the global multidimensional poverty index (G-MPI) which contains only three dimensions of welfare. But studies on the extent and determinants of rural multidimensional poverty index (R-MPI) which contains rural livelihood as one dimension of welfare are scarce. Hence, this study quantified the extent and examined the determinants of rural multidimensional poverty index using the Alkire–Foster method and the ordered logistic regression model, respectively. Data were gathered from 415 random sample households in southern Ethiopia. The incidence, intensity, and adjusted headcount ratio of rural multidimensional poverty are 72.3%, 57.3%, and 41.4% respectively. Besides, 7.47%, 20.24%, 30.60%, and 41.69% of households are non-poor, vulnerable, poor, and extremely poor, respectively. The living standard and rural livelihood dimensions jointly contributed 60% to rural multidimensional poverty. Fuel for cooking, electricity, and housing are the primary contributors to rural poverty from the living standard dimension, while land ownership, off-farm activity, and tropical livestock units are the leading contributors from the rural livelihood dimension to rural deprivation. Regression results showed that education, land size, tropical livestock unit, off-farm participation, and saving are negatively and significantly related to rural poverty, while dependency ratio, distance from market, distance from the road, and sickness of family members are positively and significantly related to rural poverty. Female-headed households were more deprived than male-headed households. Hence, promoting access to land, non-farm employment, markets, electricity, drinking water, and a road network would reduce rural multidimensional poverty in southern Ethiopia.